Incidence, risk factors, and outcome of pulmonary invasive fungal disease after respiratory virus infection in allogeneic hematopoietic stem cell transplantation recipients. Issue 5 (3rd September 2019) - Piñana, José Luis; Gómez, María Dolores; Montoro, Juan; Lorenzo, Ignacio; Pérez, Ariadna; Giménez, Estela; González‐Barberá, Eva María; Carretero, Carlos; Guerreiro, Manuel; Salavert, Miguel; Sanz, Guillermo; Hernández‐Boluda, Juan Carlos; et al.
Abstract: Background: There is growing evidence that community‐acquired respiratory virus (CARV) increases the risk of pulmonary invasive fungal disease (IFD) in the allogeneic hematopoietic stem cell transplantation (allo‐HSCT) setting. To date, there is a lack of knowledge regarding the risk factors (RFs), as well as the most critical period for subsequent onset of IFD after CARV infections in allo‐HSCT recipients. Methods: In this prospective longitudinal observational CARV survey, we analyzed the effect of CARV on subsequent IFD development in 287 adult allo‐HSCT recipients diagnosed with 597 CARV episodes from December 2013 to December 2018. Multiplex PCR panel assays were used to test CARVs in respiratory specimens. Findings: Twenty‐nine out of 287 allo‐HSCT recipients (10%) developed IFD after a CARV episode. The median time of IFD onset was 21 days (range, 0‐158 days) from day of the first CARV detection. Generalized estimating equation model identified 4 risk factors for IFD: ATG‐based conditioning regimen [odds ratio (OR) 2.34, 95% confidence interval (CI) 1.05‐5.2, P  = .038], CARV lower respiratory tract disease (OR 10.6, 95% CI 3.7‐30.8, P  < .0001), CARV infection during the first year after transplant (OR 5.34, 95% CI 1.3‐21.8, P  = .014), and corticosteroids during CARV (OR 2.6, 95% CI 1.1‐6.3, P  = .03). Conclusion: Allo‐HSCT recipients conditioned with ATG and under corticosteroid therapy at the time of CARV LRTD during the first year after transplant may require close monitoring for subsequent IFD.